Odpowiedzialność społeczna administracji publicznej na przykładzie służb statystyki publicznej - Kamiński, Stanisław (Social Responsibility of Public Administration on the Example of Public Statistics Services, 2009)
The aim of the article is to define social responsibility of public administration, which is an important part of public sector. An analysis was conducted on the example of public statistics services. The conclusion is that social responsibility of public administration is as complex issue as in case of business.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 83-88